CHEMICAL COMPOSITION OF FRESH HAIRY COCKLE (Anadara antiquata) - Rovilah, Kanza; Edison, Edison; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTHairy cockle (Anadara antiquata) one of the marine biota which unutilized optimally until now. Generally, hairy cockles are divided into five body parts, namely: foot byssus, head, digestive and reproductive parts, and shells. This study aimed to determine the chemical composition of hairy cockle meat. The method used was experimental method with two stages, namely the preparation of hairy cockle and proximate analysis. Proximate analysis was fulfilled to determine the nutritional content of which includedmoisture, ash content, protein, fat, and carbohydrates. Carbohydrate content wasanalyzedby difference. Based on the results showed that the chemical composition of hairy cockle meat had 79.34% moisture, 1.54% ash content, 11.95% protein, 2.12% fat and 5.06% carbohydrates.Keywords: Hairy cockle, Chemical composition, Proximate analysis